Labour admission test: a screening test for foetal distress in labour - Rasheed, Mohd; Srivastava, Ajay K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Labour is a very short period in the life of a foetus but poses the maximum threat. Improvements in medical technology have made it possible to monitor fetal well-being during labour. The introduction of labour admission test has proven to be of benefit in identifying patients at risk for developing distress and implementing timely intervention. Methods: The present study was undertaken to evaluate the same. This was a prospective study done on 500 patients above 37 weeks of gestation in cephalic presentation. EFM was done using oxford sonicaid 8002 CTG machine and Gem premier 3000 (model no 5700) arterial blood gas analyzer machine was used for determining the pH of fetal blood. Results: Statistical analysis was done using SPSS version 15.0 statistical analysis software. p value <0.001 was considered highly significant. Results revealed that a total of 105 (80.77%) babies had fetal distress in category II and III out of 135, whereas only 30 (8.11%) were distressed in category I out of 370. Test had a sensitivity of 77.7% and specificity of 93.15% with a positive predictive value of 80.7% and a negative predictive value of 91.89%. Conclusions: It has become evident that combined use of CTG with cord blood pH is more accurate way of predicting and diagnosing birth asphyxia.